A preliminary contribution on the marine nemas (Adenophorea) of Northern California - Chitwood, B. G. (Transactions of the American Microscopical Society, 1960)
Locality: NA; Cabinet:n112
from NeMys (AnoplostomatenuisetumC.pdf); NeMys doc_id: 4179